Practice Learning Model by Using Moving Target Media for Offensive Attack of Fencing Martial Art Assessed at Motor Ability - Ilham Kamaruddin (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study aims to determine the effect of the application of the massed practice learning model and motor ability using moving target media on fencing martial art attack skills. The research method used was an experimental method with a pre-test and post-test two group design research design. The sample used as many as 20 people with sampling techniques using simple random sample techniques through the motor ability test (Barrow Motor Ability Test). The sample was divided into two groups, namely the high motor ability group and the low motor ability group, each group consisting of ten samples. The data collection technique was using a modified fencing attack skills test (Fencing Test). The data analysis techniques in this study used the two independent sample t-test statistics. The results of this study showed that there were significant differences in the effect of the application of the massed practice learning model using moving target media in the low motor ability group and the high motor ability group. Based on the results of this study it can be concluded that the application of the massed practice learning model by using mobile target media is very effectively applied to students who have high motor skills in improving attack skills in fencing martial arts. Key Words: massed practice;motor ability;fencing attack Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran massed practice dan kemampuan motorik menggunakan media target bergerak pada keterampilan serangan bela diri anggar. Metode penelitian yang digunakan adalah metode eksperimen dengan desain penelitian dua kelompok pre-test dan post-test. Sampel yang digunakan adalah sebanyak 20 orang dengan menggunakan teknik simple random sample melalui tes kemampuan motorik (Barrow Motor Ability Test). Sampel dibagi menjadi dua kelompok, yaitu kelompok kemampuan motorik tinggi dan kelompok kemampuan motorik rendah, masing-masing kelompok terdiri dari sepuluh sampel. Teknik pengumpulan data menggunakan tes keterampilan serangan anggar yang dimodifikasi (Fencing Test). Teknik analisis data dalam penelitian ini menggunakan dua statistik uji-t sampel independen. Hasil penelitian ini menunjukkan bahwa ada perbedaan yang signifikan dalam pengaruh penerapan model pembelajaran massed practice menggunakan media target bergerak pada kelompok kemampuan motorik rendah dan kelompok kemampuan motorik tinggi. Simpulan adalah bahwa penerapan model pembelajaran massed practice dengan menggunakan media target bergerak sangat efektif diterapkan pada siswa yang memiliki keterampilan motorik tinggi dalam meningkatkan keterampilan serangan bela diri anggar. Kata kunci: massed practice;kemampuan motor;serangan anggar